2004
DOI: 10.1038/sj.eye.6701450
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of cataract extraction with intraocular lens implantation in patients with uveitis

Abstract: Objective To investigate the long-term visual results after cataract extraction in patients with uveitis, and to demonstrate the long-term viability of intraocular lenses. Design In all, 61 patients (72 eyes), with update clinical examination, were retrospectively evaluated. Comparison of preoperative, postoperative, and latest visual function including best-corrected Snellen visual acuity, progression of uveitis and its complications, need for postoperative medical or surgical interventions.Results After a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 41 publications
0
29
1
1
Order By: Relevance
“…Postoperative inflammation is linked to PCO development and has been extensively studied in uveitic eyes undergoing cataract surgery, with generally high rates of incidence being reported (ranging from 10 to 96%). 15,16 On the other hand, the incidence of PCO following 23-gauge phacovitrectomy in this study is higher than cataract surgery. Previous studies have reported that PCO developed more frequently after phacovitrectomy than after cataract surgery alone.…”
Section: Resultscontrasting
confidence: 38%
“…Postoperative inflammation is linked to PCO development and has been extensively studied in uveitic eyes undergoing cataract surgery, with generally high rates of incidence being reported (ranging from 10 to 96%). 15,16 On the other hand, the incidence of PCO following 23-gauge phacovitrectomy in this study is higher than cataract surgery. Previous studies have reported that PCO developed more frequently after phacovitrectomy than after cataract surgery alone.…”
Section: Resultscontrasting
confidence: 38%
“…In a study by Kawaguchi et al, 6 glaucoma developed in 8.4% of eyes after surgery. In a study by Rahman and Jones, 18 15.0% of patients required subsequent glaucoma drainage surgery. Our lower glaucoma rate may be the result of better control of surgery resulting from the use of the phacoemulsification technique with fixation of the IOL capsular bag.…”
Section: Discussionmentioning
confidence: 97%
“…Phacoemulsification in patients with visually significant cataract and uveitis other than Fuchs heterochromic uveitis have variable visual outcomes. [9][10][11][12][13][14][15][16][17][18][19] In this study, we excluded cases of Fuchs heterochromic uveitis because several studies have reported good surgical and visual outcomes in these cases. 7,8,21 In our series, successful phacoemulsification was completed in all cases and the IOL was implanted in the capsular bag except in 1 eye in which posterior capsule rupture occurred during I/A of the cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rate has been reported as 23.7% by Kawaguchi et al 31% by Estafounus et al and 96% by Rahman et al Hydrophilic acrylic intraocular lenses worked well in eyes with higher uveal biocompatibility, but PCO development was greater than in eyes with hydrophobic acrylic IOLs. 5,20,25,26 It is known that PCO development is seen least commonly with hydrophobic IOLs and with sharp optic edges. [26][27][28][29] A hydrophobic acrylic lens had been used in all our patients.…”
Section: Discussionmentioning
confidence: 99%